2022
DOI: 10.3389/fphar.2022.783679
|View full text |Cite
|
Sign up to set email alerts
|

Understanding the Gut-Kidney Axis in Antineutrophil Cytoplasmic Antibody-Associated Vasculitis: An Analysis of Gut Microbiota Composition

Abstract: Increasing evidence suggested that gut microbiota played critical roles in developing autoimmune diseases. This study investigated the correlation between gut microbiota and antineutrophil cytoplasmic antibody-associated vasculitis (AAV) with kidney injury. We analyzed the fecal samples of 23 AAV patients with kidney injury using a 16s RNA microbial profiling approach. The alpha-diversity indexes were significantly lower in AAV patients with kidney injury than healthy controls (Sobs P < 0.001, Shannon P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
17
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(18 citation statements)
references
References 41 publications
1
17
0
Order By: Relevance
“…Oscillospira, a genus capable of synthesizing short-chain fatty acids like butyrate, has been linked to inflammation-related disorders, such as inflammatory bowel disease, non-alcoholic fatty liver disease, and aging processes distinguished through increased levels of circulating inflammatory mediators (Chierico et al, 2017 ; Lima and Longman, 2021 ; Xu et al, 2021 ), and is strongly negatively associated with pro-inflammatory monocyte chemoattractant protein-1 (Buford, 2017 ). Deltaproteobacteria were found to be negatively related to antineutrophil cytoplasmic antibody-associated vasculitis (AAV) with kidney injury (Yu et al, 2022 ). The herbal tea ingredient Rabdosia serra acts as an anti-inflammatory agent by boosting the number of helpful bacteria, such as Lactobacillus, as well as reducing the number of harmful bacteria including Eubacterium xylanophilum , thus alleviating artificially induced colitis in mice (Li et al, 2022 ).…”
Section: Discussionmentioning
confidence: 99%
“…Oscillospira, a genus capable of synthesizing short-chain fatty acids like butyrate, has been linked to inflammation-related disorders, such as inflammatory bowel disease, non-alcoholic fatty liver disease, and aging processes distinguished through increased levels of circulating inflammatory mediators (Chierico et al, 2017 ; Lima and Longman, 2021 ; Xu et al, 2021 ), and is strongly negatively associated with pro-inflammatory monocyte chemoattractant protein-1 (Buford, 2017 ). Deltaproteobacteria were found to be negatively related to antineutrophil cytoplasmic antibody-associated vasculitis (AAV) with kidney injury (Yu et al, 2022 ). The herbal tea ingredient Rabdosia serra acts as an anti-inflammatory agent by boosting the number of helpful bacteria, such as Lactobacillus, as well as reducing the number of harmful bacteria including Eubacterium xylanophilum , thus alleviating artificially induced colitis in mice (Li et al, 2022 ).…”
Section: Discussionmentioning
confidence: 99%
“…They also established a random forest model algorithm based on operational taxonomic unit (OUT) markers for the diagnosis and prediction of disease activity in MPA, which showed good predictive power (Yu et al, 2021). Another study also reported a gut-kidney axis in AAV, showing that changes in gut microbiota composition are associated with the degree of renal injury in AAV patients; this suggested that targeted regulation of gut dysbiosis may be a new intervention to reduce kidney damage in AAV patients (Yu et al, 2022).…”
Section: Anca-associated Vasculitismentioning
confidence: 99%
“…Culturing these mice in a germ-free condition or with antibiotic treatment can significantly downregulate the Th17 cells and relieve kidney inflammation, while Citrobacter rodentium infection can expand Th17 cells and aggravate kidney damage in mice (Krebs et al, 2016). Some cross-sectional studies have proved that alterations of gut microbiota (including reduced SCFAproducing taxons) existed in AAV and were also linked to kidney injury (Table 2) by analyzing the fecal samples of patients using 16s rRNA sequencing (Najem et al, 2018;Yu et al, 2021;Yu et al, 2022) (Yu et al, 2021). They also established a random forest model algorithm based on operational taxonomic unit (OUT) markers for the diagnosis and prediction of disease activity in MPA, which showed good predictive power (Yu et al, 2021).…”
Section: Anca-associated Vasculitismentioning
confidence: 99%
“…Gut leaky may cause a series of immune-related diseases, such as systemic lupus erythematosus (SLE) (55) and ANCA-associated vasculitis (AAV) (56).…”
Section: Leaky Gutmentioning
confidence: 99%